Fragmentation method of coral (Caulastrea furcata) for growth measured at controlling condition - Zulfikar, Zulfikar; Soedharma, Dedi; Yasin, Zulfigar; Tan Shau Hwai, Aileen (Universitas Malikussaleh, 2014)
The objective of the research are: (1) to analyze the water quality condition of water circulation system at laboratory and (2) to measure the growth (length and height) and survival rate of Caulastrea furcata which was fragmented at the laboratory. The water quality condition at the laboratory showed that every parameter has normal value in which organism can live and grow. Natural feed such as Copepoda and Nannoclhoropsis were also cultured at the laboratory as food for the coral. Transplantation was done by cutting the colony of coral or by breaking the branch of coral into pieces from every kind of coral spesies and placed those on artificial substrate made from ceramic bricks. Cutting process was done after the acclimatization process. Fragmentation treatment of C. furcata become 1 polyp, 2 polyp, 3 polyp and 4 polyp that was reared on circulation system did not give significant impact on height and length growth after 160 days. Mean of growth length of C. furcata on treatment 1, 2, 3 and 4 polyps in every month after 160 days was 1.64 mm, 1.55 mm, 1.42 mm and 1.08 mm, respectively, whereas mean of growth broad was 0.71 mm, 0.82 mm, 0.51 mm and 0.62 mm, respectively. Fragmentation treatment of C. furcata become 1 polyp was best length if compare other treatment.Tujuan penelitian ini adalah: (1) menganalisis kondisi kualitas air pada system sirkulasi air di laboratorium dan (2) mengukur pertumbuhan (panjang dan tinggi) dan tingkat kelulushidupan Caulastrea furcate yang telah difrakmentasi di laboratorium. Nilai kualitas air menunjukkan bahwa setiap parameter adalah normal dan dapat mendukung kehidupan dan pertumbuhan organisme. Pakan alami seperti Copepoda dan Nannoclhoropsis yang juga dikultur di laboratorium sebagai pakan karang. Tansplantasi dilakukan melalui pemotongan koloni karang pada bagian cabang karang kedalam bagian kecil dari setiap spesies karang dan ditempatkan pada subtrak buatan yang dibuat dari keramik. Proses pemotongan dilakukan setelah proses aklimatisasi dilakukan. Perlakuan frakmentasi C. furcate menjadi 1 polip, 2 polip, 3 polip dan 4 polip kemudian didedahkan dalam air berskirkulasi tidak memberikan efek yang signifikan terhadap pertumbuhan tinggi dan panjang setelah 160 hari. Rata-rata pertambahan lebar pada perlakuan 1, 2, 3 dan 4 polip pada setiap bulan setelah 160 hari adalah 1.64 mm, 1.55 mm, 1.42 mm dan 1.08 mm. dimana rata-rata pertumbuhan tinggi secara berurutan adalah 0.71 mm, 0.82 mm, 0.51 mm dan 0.62 mm. Perlakuan frakmentasi 1 polip pada C. furcate menghasilkan panjang terbaik dibandingkan perlakuan lainnya.